2013
DOI: 10.1371/journal.pone.0081701
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Nucleosides as Biomarkers of Breast, Colon, Lung, and Gastric Cancer in Taiwanese

Abstract: Urinary nucleosides are associated with many types of cancer. In this study, six targeted urinary nucleosides, namely adenosine, cytidine, 3-methylcytidine, 1-methyladenosine, inosine, and 2-deoxyguanosine, were chosen to evaluate their role as biomarkers of four different types of cancer: lung cancer, gastric cancer, colon cancer, and breast cancer. Urine samples were purified using solid-phase extraction (SPE) and then analyzed using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 15 publications
0
36
1
Order By: Relevance
“…Pathological verification of urogenital tract cancer was completed by biopsy or surgical resection of tumors (see details in Table 1). The Tumor-Node-Metastasis (TNM) classification (American Joint Committee on Cancer), as well as tumor grading system, were used in order to establish the stage and grade of the disease [17][18][19]. Patients were classified by disease stage into two subphenotypes: those diagnosed from T1 stage and those for whom the stage was above T1.…”
Section: Study Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pathological verification of urogenital tract cancer was completed by biopsy or surgical resection of tumors (see details in Table 1). The Tumor-Node-Metastasis (TNM) classification (American Joint Committee on Cancer), as well as tumor grading system, were used in order to establish the stage and grade of the disease [17][18][19]. Patients were classified by disease stage into two subphenotypes: those diagnosed from T1 stage and those for whom the stage was above T1.…”
Section: Study Participantsmentioning
confidence: 99%
“…Seidel et al [48] reported different nucleosides' excretion pattern within the same stage of a disease, suggesting determination of more than four nucleoside profiles in order to evaluate the disease status. Likewise in [38], Hsu et al [18] postulated that studies should be limited to one particular type of disease due to the occurrence of variations in urinary nucleoside levels between breast, colon, lung and gastric cancer patients and healthy individuals. Different sets of nucleosides, significantly associated with different cancer types were identified with the exception for urinary nucleoside profile in gastric and lung cancer patients, for which the profile was similar [18].…”
Section: A (μM/mm) N2mg (μM/mm) Case (%) Control (%) or (95% Ci) P-vamentioning
confidence: 99%
See 2 more Smart Citations
“…The most popular analytical column is C18 [6,[15][16][17][18][19][57][58][59], however HILIC columns are becoming more popular due to the polar character of compounds like nucleosides [55,60]. Besides, there is also a trend to resemble conditions like UHPLC using routine HPLC system in order to reduce eddy-diffusion and increase flow rates with controlled back pressures.…”
Section: Sample Pretreatment Procedures and Stationary Phases For Urinmentioning
confidence: 99%